Особенности подготовки медицинских специалистов при оказании паллиативной помощи в Украине в период пандемии - Гура, Татьяна Витальевна (Impressum, 2020)
The article shows the relevance of providing palliative care in the world with pandemics. The history of the development of palliative care in Ukraine is presented. Special attention is paid to the content of the concept of “Palliative care”. The necessity of providing psychological assistance and psychological support to dying patients and their relatives is proved. The questions of urgent training of paramedical workers in medical colleges of Ukraine related to palliative care are highlighted. The necessity of developing new curricula taking into account the formation of psychological competence in future medical workers is proved.
Keywords: educational process; palliative care; palliative training; students of medical colleges; psychological assistance; psychological support; psychological preparation; pandemic